THE INFLUENCE OF INNER ORGANIZATIONAL COMMUNICATION IMPROVING TEACHER PERFORMANCE - Muhidin Muhidin; Irian Nasri; Hendriansyah Hendriansyah; Dora Indah Triana (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research tests the analysis of the influence of organizational communication in improving teacher performance. This research was conducted at SMKN I Sungai Lilin, Banyuasin Regency with a sample of 34 respondents. The results obtained from regression analysis using the SPSS version 22 tool show that there is an influence of Organizational Communication in improving Teacher performance. Where the R results in simple linear regression analysis show a correlation between two independent variables on one dependent variable. The R number obtained is 0.527, this means that there is a strong relationship because the value is close to 1. Meanwhile, the R Square (R2) results show the value of the coefficient of determination. This figure will be converted into a percentage, which means the percentage contribution of the influence of the dependent variable. The R2 value is 0.278, meaning that the influence of organizational communication in improving teacher performance is 27.8%, while the rest is influenced by other variables not included in this research. The data obtained in this research comes from the answers to questionnaires distributed to each respondent. according to the results of statistical analysis, the results of the linear regression equation Y = 0.620 + 0.927